A historical and legal study of sovereignty in the Canadian north : terrestrial sovereignty, 1870–1939 - Smith, Gordon W. (University of Calgary Press, 2014)
Gordon W. Smith, PhD, dedicated much of his life to researching Canada’s sovereignty in the Arctic. His 1952 dissertation from Columbia University on “The Historical and Legal Background of Canada’s Arctic Claims” remains a foundational work on the topic, as does his 1966 chapter “Sovereignty in the North: The Canadian Aspect of an International Problem” in R. St. J. Macdonald’s The Arctic Frontier. A Historical and Legal Study of Sovereignty in the Canadian North is the first in a project to edit and publish Smith’s unpublished opus – a manuscript on sovereignty and related Law of the Sea issues. Researched and written over three decades, this comprehensive and thoroughly documented study offers important insights into evolving understandings of Canada’s sovereignty from the original transfers of the northern territories to the young dominion through the start of the Second World War. With Arctic issues once again at the forefront of public debate, this invaluable resource – available to researchers outside of government for the first time – explains how Canada laid the historical and legal foundations to support its longstanding, well-established sovereignty over Arctic lands. 2014-11-17 Yes Arctic Institute of North America